PENGARUH KUALITAS INFORMASI DARI HUMAS PT. KALBE FARMA DI MEDIA SOSIAL INSTAGRAM TERHADAP KEPERCAYAAN KONSUMEN - Laura Christie (2020)
This research is motivated by quality information that must have three things that are accurate, relevant, and right on time. Public Relations of PT. Kalbe Farma provides information to consumers on social media Instagram must have that. The purpose of this research is to study how big is the influence of the quality of information at PT. Kalbe Farma through social media Instagram on consumer trust. The theory in this study uses the theory of information integration. This research method uses quantitative research methods with the type of explanative research. The sample in this study was 99 respondents with a random sampling technique that collected data using a questionnaire. Based on the results of this study indicate that between the quality of PR information PT. Kalbe Farma through social media Instagram on consumer trust.